Pars plana incisions of four patients: histopathology and electron microscopy. Issue 5 (May 1995) - Koch, F H; Kreiger, A E; Spitznas, M; Glasgow, B; Foos, R Y; Yoshizumi, M O
Abstract : The pathology of pars plana incisions of four patients is described: three with light microscopy and one with light and electron microscopy. Two eyes were removed because of choroidal melanoma, immediately and 8 days after vitrectomy and transvitreous retinal biopsy. Considerable disruption of tissues surrounding the pars plana incisions was observed. Vitreous was incarcerated in the wounds, which healed with granulation tissue. One eye was examined 4 months after vitrectomy for diabetic retinopathy and a failed pars plana filtering operation. It contained fibrovascular ingrowth from all the incisions, infiltrating the vitreous base with granulation tissue and causing vitreous haemorrhage and retinal detachment. One eye was removed 1 year after vitrectomy for anterior hyaloidal fibrovascular proliferation and early phthisis. The wound had fibrous ingrowth histologically and evidence of active fibroplasia.